Hubungan Tipe Kepribadian dengan Perilaku Seksual Berisiko Remaja di SMKN “X” Jember (The Correlation of Personality Type with Risk Sexual Behavior of Adolescence at SMKN "X" Jember) - Alvivo Darma Chandra; Iis Rahmawati; Ratna Sari Hardiani (Pustaka Kesehatan, 2014)
Adolescent is a period of transition from child to adult. Change of adolescent is sign with thesexual organs. Adolescent not only identified the physical changes, but also the psychological.One of that is risk sexual behavior in adolescent, Risk behavior sexual can bring consequencesthat unwanted abortion, pregnancy outside of marriage, of contracting sexually transmitteddiseases (STDs), and HIV / AIDS. One of the factors that influence adolescent sexual behavioris personality which consists of extrovert and introvert. The purpose of this research was todetermine the correlation of personality types with risk adolescent sexual behavior. Thisresearch design was a descriptive analytic study using cross-sectional approach. The samplesare 68 respondents,Sampling technique used multistage random sampling. The instrumentused a questionnaire sheet. Analysis of bivariate data used chi square test showed that thevalue of ρ value = 0.001 (<α=0.05) and odd ratio (OR) = 7,556, so it can be concluded thatthere is a correlation between personality type with risk sexual behavior of adolescence atSMKN "X" Jember. This research suggested to the health employee is to promote reproductionof sexual education for decrease risk sexual behavior.Keywords: Personality Type, Risk Sexual Behavior, Adolescent